Research and Application of Foam Filling Material in Soft Rock Roadways - Changyu Li; Hua Nan; Wenzhou Zhang (Applied Sciences)
Due to the soft mechanical properties of soft rock strata, roof fall accidents are frequent, causing great hazards to production. In order to eliminate hazards in the actual mining process, a new type of bag-filling scheme was designed by analyzing the mechanisms of roof falls in soft rock strata. By testing the filling material, the optimal ratio of foam filling material was determined, and the corresponding filling process was formulated. Through the field verification of this filling process, better support was achieved in the roof fall area, providing useful guidance and support for mines with similar conditions.